2015
DOI: 10.1253/circj.cj-15-0056
|View full text |Cite
|
Sign up to set email alerts
|

Noncardiac Comorbidities in Heart Failure With Preserved Ejection Fraction – A Commonly Ignored Fact –

Abstract: It has been well described that many patients with heart failure (HF) have a normal left ventricular ejection fraction. This entity has been termed "heart failure with preserved ejection fraction (HFPEF)". Significant advances have been made in understanding the clinical characteristics of HFPEF over the past 2 decades on the basis of large HF registries and randomized clinical trials. However, most multicenter clinical trials that investigated medical therapies in HFPEF have yielded disappointing results. HFP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 62 publications
0
15
0
3
Order By: Relevance
“…42 Non-cardiac comorbidities may be a possible explanation for treatment failure of CHF patients. 43 Thus, it is important to elucidate the mechanism of depression and cognitive impairment, which are the major brain comorbidities of CHF patients. The present study demonstrated that a novel neural substrate, the hippocampus, could explain the association between CHF and depression and cognitive dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…42 Non-cardiac comorbidities may be a possible explanation for treatment failure of CHF patients. 43 Thus, it is important to elucidate the mechanism of depression and cognitive impairment, which are the major brain comorbidities of CHF patients. The present study demonstrated that a novel neural substrate, the hippocampus, could explain the association between CHF and depression and cognitive dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…11−17 In patients with HFpEF, it has been estimated that approximately only 10-25% of cases of hyponatremia are reported. 14, 18 Several recent clinical studies demonstrated that hyponatremia is an independent predictor of mortality in HFpEF patients and that sNa at admission for acute HF predicted the likelihood of cardiovascular death, with a relative risk for cardiovascular death of 1.08 for each 1-mmol/L decrease. 14, [19][20][21][22][23] In HFpEF patients after treatment according to the guideline, we investigated the prognostic significance of sNa as a continuous variable and low-normal sNa (135 mmol/L<sNa <140 mmol/L) for HF-related clinical events.…”
Section: Discussionmentioning
confidence: 99%
“…4-6 The pathophysiological base of HFpEF may be an extreme form of age-related deterioration with ventricular-arterial interrelation, possibly related to the prevalence of noncardiac comorbidities. 7 Regression modeling has identified that changes in cardiac structure, such as greater LV hypertrophy (LVH) and atrial dilation, best distinguish HFpEF from hypertensive LVH without HF. 8 However, the difference between elderly men and women in diastolic function relative to arterial elasticity, and its relation to alterations in the cardiac structure of hypertensive patients, remains unclear.…”
Section: Arterial Elasticity-related Diastolic Functionmentioning
confidence: 99%